Art and Society: The Idea of Form in Adorno’s Aesthetical Theory - Piazza, Anna (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This article aims to demonstrate how the aesthetical theory of Theodor Adorno represents the very nucleus of Adorno’s “sociological philosophy”. I show why artworks, thanks to the ontological and material elements that constitute them, are the privileged point to comprehend the factors at play in society. In order to achieve this, I investigate particularly the concept of form. With this, I underline how the character of “open form” of modern art claimed by Adorno, though being a manifestation of a contingent historical moment, is able to deeply reflect the character of “openness” of reason, which thus conjugates with the proper function of philosophy.